Healthcare Employee and Patient Rights - Yeyit, Sevval; Kacan, Havva (Nobel Tip Kitabevleri, 2024)
Recommendations about the attitudes of healthcare staff and patients toward patient rights within the scope of patient rights and the current status of patient rights are dis- cussed in this section. The correlation between healthcare staff and patients, patient rights regulations of countries, attitudes of healthcare staff and patients toward patient rights and related factors, the most frequently violated patient rights and ethical problems are emphasized. The section also involves the ethical dilemmas faced by healthcare staff when defending patient rights, situations that cause ethical dilemmas, and attitudes on this is- sue, and emphasizes that patient rights are based on human rights and are a medical re- flection of human rights. It is argued that patient rights are universal for every individual, but perceptions of patient rights might change depending on individual characteristics. As a result, recommendations are included to raise awareness and strengthen healthcare staff and patients about patient rights.